Recurrent Spontaneous Coronary Artery Dissection as the Cause of Repeated Myocardial Infarctions - Arnon Møldrup Knudsen; Nicolaj Brejnholt Støttrup; Henrik Hager; Henning Mølgaard; Christina Stilling (Clinical Case Reports)
ABSTRACT Spontaneous coronary artery dissection (SCAD) is characterized by intramural hematoma in a coronary artery leading to partial or complete vessel obstruction. A 51‐year‐old female was hospitalized with acute myocardial infarction and cardiogenic shock. She was diagnosed with severe SCAD, affecting the proximal left coronary artery. A complex percutaneous coronary intervention, complicated by cardiac arrest and need for cardio pulmonary support, succeeded with stent insertion and revascularization. In the following days, the patient developed severe heart failure due to extensive cardiac reperfusion injury and subsequently experienced multiple organ failure, ultimately resulting in death. The patient had previously been acutely hospitalized twice with myocardial infarctions and both the times was also diagnosed with SCAD affecting the left coronary artery. This case highlights an unfortunate patient outcome due to recurrent SCAD and serves as an important reminder to consider SCAD differential diagnostically in younger female patients with myocardial infarction.